A prática da gestão no cotidiano de uma escola pública de Guarulhos - Oliveira, Thiago Aparecido de (2017)
The object of this research is the practice of the management team of a state elementary school, located in the city of Guarulhos, metropolitan region of São Paulo. The methodology is based on a field research within the school that was the focus of participant observation, considering that I am part of the teaching staff. As a data collection instrument, structured interviews were conducted involving four members of the management team, one director, one deputy director and two coordinators. The general objective is to analyze the management team's practice and its effort to understand the challenges of seeking partnerships between parents, students and employees that work within the school analyzed. The specific objectives are to analyze the management team's view on their own practice and to verify if the dialogic relations are part of the daily school life. Hypothesis: considering that the work of the management team is procedural and historical, we assume that the promotion of communication in the interrelationships between the subjects of the pedagogical action is weakened by the lack of understanding of the dynamics of the process that generates democracy in the school. Faced with this statement it is necessary to discuss the management practice, regarding the organizational model of the current public school. We analyze and discuss the practices of school management as possibilities of advancement in the quality of education. In this context, we list two problems, namely: does the practice of the management team contemplate the basic education of the school? From the legal point of view, do the existing laws subsidize the specificities of school learning? We analyzed government documents and determinations that concern the school and support the management practice: Federal Constitution of 1988; Law of Guidelines and Basis of National Education of 1996 (LDBEN); National Education Plan 2014/2024 (PNE); Political-pedagogical project (PPP). This research concludes that the management team can advance with respect to the principle of democracy in the school, appropriating itself, of conceptual references to identify the obstacles that are placed in the quotidian of the dialogical relations. It is also noted the need for actions that organize collective work and promote rapprochement with the community.